The Role of Risk Litigation in Merger and Acquisition (M&A) Valuation : An Overview Strategic in Opinion Fairness in Merger and Acquisition Transactions - Clarencia Angelika; Yessica Amelia (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review explores the role of litigation risk in merger and acquisition (M&A) valuations, focusing on fairness opinions. The study reveals that high litigation risk leads to lower valuations in target-sought fairness opinions, particularly in transactions with significant agency conflicts. Regulatory changes, such as those in Delaware, have increased awareness of litigation risks and influenced valuation strategies. The selection of peer firms for valuation is also affected by litigation risk, underscoring the importance of accurate peer selection. These findings provide valuable insights for academics, practitioners, and policymakers in managing litigation risk and maximizing value in M&A transactions. Limitations include reliance on existing literature and potential contextual differences across jurisdictions. Future research should empirically test these hypotheses and explore other jurisdictions to gain a comprehensive understanding of litigation risk in M&A valuations.